Correlation Test Application of Supplier’s Ranking Using TOPSIS and AHP-TOPSIS Method - Yuniwati, Ika (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2016)
The supplier selection process can be done using multi-criteria decision making (MCDM) methods in firms. There are many MCDM Methods, but firms must choose the method suitable with the firm condition. Company A has analyzed supplier’s ranking using TOPSIS method. TOPSIS method has a marjor weakness in its subjective weighting. This flaw is overcome using AHP method weighting having undergone a consistency test. In this study, the comparison of supplier’s ranking using TOPSIS and AHP-TOPSIS method used correlation test. The aim of this paper is to determine different result from two methods. Data in suppliers’ ranking is ordinal data, so this process used Spearman’s rank and Kendall’s tau b correlation. If most of the ranked scored are same, Kendall’s tau b correlation should be used. The other way, Spearman rank should be used. The result of this study is that most of the ranked scored are different, so the process used Spearman rank p-value of Spearman’s rank correlation of 0.505. It is greater than 0.05, means there is no statistically significant correlation between two methods. Furthermore, increment or decrement of supplier’s ranking in one method is not significantly related to the increment or decrement of supplier’s ranking in the second method